Transformasi Kurikulum Fisika di Indonesia: Kajian dari KTSP hingga Kurikulum Merdeka - Andi Ulfah Khuzaimah; Mukti Ali; Nurul Kami Sani (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2025)
The transformation of Indonesia's curriculum reflects the dynamics of social change, advancements in science and technology, and the evolving demands of globalization. This study aims to examine the development of the physics curriculum at the senior high school (SMA) level, starting from the School-Based Curriculum (KTSP), the 2013 Curriculum (K13), the Revised 2013 Curriculum, to the Merdeka Curriculum. The research employs a Systematic Literature Review (SLR) approach by analyzing various relevant academic sources. The review focuses on four key components of curriculum development: learning objectives, learning materials, teaching methods, and assessment strategies. The findings indicate that the Merdeka Curriculum offers the highest level of flexibility, with a more contextual, student-centered learning approach emphasizing project-based activities and self-reflection. In contrast, KTSP is characterized by a more rigid structure with limited room for innovation. The 2013 Curriculum and its revision fall between the two, maintaining a scientific approach and authentic assessment that remain relevant but are less flexible. This study recommends intensive teacher training and the broader implementation of the Merdeka Curriculum to make physics education more effective, adaptive, and meaningful.